Peran Kh Abd. Majid Mz Dalam Mencetak Kader-Kader Tilawah Di Pondok Pesantren Raudlatut Tholabah - Ahmad Arifin, Rafi; Tofaynudin, Johan Indrus (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research discusses the role of KH Abd. Majid MZ in the development of tilawah cadres at the Raudlatut Tholabah Islamic Boarding School. KH Abd Majid MZ is known as a clerical figure who has high dedication in the field of Qur'anic education, especially in the art of reading the Qur'an or tilawah. Through a holistic and systematic approach, he succeeded in creating a conducive and inspiring learning environment for his students. This study uses a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation. The results showed that KH Abd. Majid MZ not only acts as a teacher, but also as a mentor who provides moral and spiritual guidance to the students. The teaching methods applied include routine coaching, intensive training, and periodic evaluations that are able to significantly improve the students' recitation skills. KH Abd. Majid MZ is also active in organizing various activities that support the development of tilawah, such as tilawah competitions, seminars, and workshops involving leading tilawah experts and practitioners. His contribution is not only felt at the local level, but also at the regional and national levels, given the number of tilawah cadres who have achieved achievements in various competitions. This study concludes that the character of KH Abd. Majid MZ in producing recitation cadres is very significant and has a broad impact in improving the quality of Qur'anic education at the Raudlatut Tholabah Islamic Boarding School. His dedication and commitment in developing tilawah inspires the younger generation to continue to explore and love the Qur'an.